IMPROVING CRITICAL THINKING SKILLS AND LEARNING OUTCOMES USING SCIENCE,TECHNOLOGY, AND SOCIETY (STS) LEARNING MODEL ON THE 5TH GRADE ELEMENTARY SCHOOL STUDENTS - Siti Hanifa Ari Utami; Mawardi Mawardi; Suhandi Astuti (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract: This study are aims to improve the critical thinking skills and students’ learning outcomes using the Science, Technology, and Society (STS) learning model on the 5th grade students of SDN Dukuh 05 Salatiga. The type of this research is a Classroom Action Research (CAR). The data were collected through tests, observations, and documentations. The instrument that used in this research is questionnaire sheets of critical thinking skills with the total of 25 statements and the evaluation questions with the total of 20 questions. The data analysis was carried out by qualitative and quantitative analysis. This research was conducted in two cycles. Obtaining the mean score of critical thinking skills of students in the first cycle are 62, 96 (enough). Then in the second cycle increased to 75 (high). Furthermore, the students’ learning outcomes also increase, which can be seen from the grade mean scores and the number of students who get score above the Minimum Criteria of Mastery Learning ≥ 66. Ratio of the percentage of completeness in the first cycle is 48% with the mean score of 70.2, then in the cycle II increased to 84% with the mean score of 80.8. In this research was concluded that critical thinking skills and learning outcomes are improved after the learning action of the Science, Technology, and Society (STS) learning model. Keywords: Critical thinking, Science, Technology, and Society (STS).